2014
DOI: 10.5430/jnep.v4n5p85
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and opinions of health professionals in relation to the presence of the family during in-hospital cardiopulmonary resuscitation: An integrative review

Abstract: The presence of the family during cardiorespiratory resuscitation efforts has been reported for more than twenty years and, despite a lack of strong evidence of its benefit, the tendency to not permit this practice has been observed. The aim of this review is to identify studies in the global literature performed about the experiences and opinions of nurses and other health professionals regarding the presence of the family during intra hospital cardiorespiratory arrest. An integrative review according to step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…Many studies present this dichotomy of understanding, especially when they investigate the perception of different actors, such as professionals versus family versus patients (24) , or even from different professional categories, such as nurses versus doctors (25,32) . An integrative review study with 14 studies showed that nurses were more likely to accept family presence than doctors, and that care nurses were less supportive of the practice than those in managerial and research positions (34) . This difference is certainly a reflection of the greater or lesser awareness about PFCC and the importance given to the patient's family, including during cardiopulmonary resuscitation and invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies present this dichotomy of understanding, especially when they investigate the perception of different actors, such as professionals versus family versus patients (24) , or even from different professional categories, such as nurses versus doctors (25,32) . An integrative review study with 14 studies showed that nurses were more likely to accept family presence than doctors, and that care nurses were less supportive of the practice than those in managerial and research positions (34) . This difference is certainly a reflection of the greater or lesser awareness about PFCC and the importance given to the patient's family, including during cardiopulmonary resuscitation and invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of an integrative review of multiple studies reported that the majority of providers disagreed with family presence during resuscitation. 1 Yet, despite these data, studies of families who actually witnessed resuscitation efforts have shown clear benefits for the families who are present. In a randomized controlled trial of 570 individuals, participants were divided into 2 groups: those receiving typical interaction with the care team with resuscitation and those who were specifically invited to witness the resuscitation.…”
Section: Recent Research On Family-witnessed Resuscitationmentioning
confidence: 97%
“…Benefits to families include improved communication about the patient's health status and promotion of a healthy grieving process. 1 Nevertheless, only a small percentage of intensive care units (ICUs) have policies promoting family-witnessed resuscitation (FWR), in large part because of concerns about risks to visitors and staff if families are allowed to be present during resuscitation efforts. Areas of concern include emotional distress to the family, additional people obstructing resuscitation efforts, and exposure of staff to medicolegal risk.…”
mentioning
confidence: 99%
“…Ever since its first implementation in the 1980s1 family presence during cardiopulmonary resuscitation (CPR) remained a controversial issue 2–4. Current guidelines recommend that family members should be offered the option to be present during resuscitation in situations where it is safe, and when the family can be adequately supported 5–7.…”
Section: Introductionmentioning
confidence: 99%
“…CPR is a demanding and often stressful task14 15 and the presence of a family member may add cognitive and emotional demands. Data available are conflicting and cover the range from no perceived additional stress to perceived significant hampering one’s own activity due to family presence 1 4 8 16. So far, there are no apparent negative effects on patients’ outcomes in hospitals that allow families to be present during CPR 17 18.…”
Section: Introductionmentioning
confidence: 99%